Keberagaman Pengguna Ruang Publik Permukiman Di Atas Air Berkepadatan Tinggi - Fauzi, Hendri; Siregar, Johannes Parlindungan; Wardhani, Dian Kusuma (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2014)
Tarakan City is the most developed region in northern Borneo with great potential that has a fascination for outsiders to enter Tarakan City. It has potential as a region with a high density, so it will be difficult to provide a public space with a common interest due to the limited space. Activities undertaken communities are able to support social activities and behaviors with some activity. Capable of forming a social space that is used together are categorized as public spaces that accommodate the specific activity of the community either individually or in groups, by age and gender. The purpose of this study is to identification the diversity of the user based on the typology of space and activity patterns of public space were observed. Assessment of the diversity of users using the Simpsons Diversity Index with data from observations. This study suggested that the high density conditions with the type of settlement that is in the water it was found that users of public space in the sub- blocks of different studies have diversity in each sub- tract.Keywords: Public Space, simpsons diversity index, diversity of users, typology of space